Impact of antibiotic allergy labels on patient outcomes in a tertiary paediatric hospital. Issue 3 (9th September 2021) - Catalano, Anthony C.; Pittet, Laure F.; Choo, Sharon; Segal, Ahuva; Stephens, David; Cranswick, Noel E.; Gwee, Amanda
Abstract : Aims: Antibiotic allergies are reported in 5–15% of children. This study aimed to evaluate the impact of common β‐lactam antibiotic allergy labels (AALs) on hospital treatment, focusing on length of stay and appropriateness of antibiotic prescribing. Methods: This was a retrospective cohort study over 21 months at the Royal Children's Hospital Melbourne, Australia. A subset of children with the most common β‐lactam allergies, and who required admission for intravenous antibiotics over a 12‐month period, was analysed for appropriateness of prescribing. Non‐allergic patients were matched to evaluate associations between AALs and hospital treatment. Results: There were 98 912 children admitted over the study period, of whom 938 (1%) had at least one AAL on first admission. Of all encounters, 5145 (2.5%) were for children with AALs. The most common AALs were to amoxicillin and amoxicillin‐clavulanic acid combinations (40.8%), cefalexin (14.4%) and trimethoprim‐sulfamethoxazole (9.7%). For the subset, there were 66 admissions for children who required intravenous antibiotics. Documentation was adequate for 27% of AALs. Inappropriate prescribing occurred in almost half (47%). Hospital stay was longer for children with AALs (median 4.7 days; IQR 2.3–9.2) compared to non‐allergic controls (median 3.9 days; IQR 1.9–6.8; P = .02). Children with AALs were more likely to receive restricted antibiotics (aOR 3.03; 95% CI, 1.45–6.30; P = .003). Conclusion: This is the first study to demonstrate high rates of inappropriate prescribing in children with AALs. Children with AALs were significantly more likely to receive restricted antibiotics and had a longer length of stay compared with non‐allergic controls.